The investigation of stereogenic properties of cyclotriphosphazene derivatives with two different chiral centres - Un, Sule Sahin; Uslu, Aylin; Yeşilot, Serkan; Un, Ilker; Cosut, Bunyemin; Yüksel, Fatma; Kilic, Adem (Pergamon-Elsevier Science Ltd, 2011)
Hexachlorocyclotriphosphazene N3P3Cl6 and gem-disubstituted cyclotriphosphazene derivatives N3P3Cl4X2 (X = Ph, PhS, PhNH) were reacted with N-methyl-1,3-propanediamine and 3-amino-1-propanol to give compounds (9a-12a, 9b-12b) which exist as cis and trans geometric isomers and are two different racemic isomers, respectively to describe the stereogenic properties of a series of chiral cyclotriphosphazene compounds with two different centres of chirality. The geometric isomers were separated by column chromatography on silica gel and analysed by elemental analysis, mass spectrometry, and P-31 and H-1 NMR spectroscopies, and also the geometric forms (cis or trans) of 9b, 10a, 11a, 11b and 12a have been determined by the X-ray crystallography. The enantiomers of all racemic compounds have been analysed by the changes in P-31 NMR spectra on addition of a Chiral Solvating Agent (CSA), (R)-(+)-2,2,2-trifluoro-1-(9'-anthryl)ethanol. On the other hand, the racemic forms of chiral cyclotriphosphazene derivatives have been confirmed by contribution of chiral HPLC methods which have been developed for this study. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cyclotriphosphazene; Chirality; X-ray; CSA; Chiral HPLC